1970
DOI: 10.1148/94.3.575
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Collaterals in the Liver Hilus

Abstract: Arterial collaterals in the hilus of the liver may develop in a variety of clinical situations including neoplasm, atherosclerosis, operative ligation and other vascular stenoses, and cirrhosis. They are normally present but are not demonstrated angiographically unless they are functioning as collaterals. Hilar collaterals are an important factor in maintaining liver viability following accidental or purposeful hepatic arterial ligation. The authors base their discussion on personal experience with 16 cases. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 3 publications
0
33
0
2
Order By: Relevance
“…Angiography demonstrated the interlobar branch-relayed collateral blood flow between the hepatic arteries [31][32][33][34][35][36][37] to be readily noted at the occlusion of either of the hepatic arteries [32,33,37] , which was demonstrated by computerized tomographic angiography in our Case 2 ( Figure 11). The interlobar arterial collaterals may be responsible for the poor distribution of a chemotherapeutic agent at its selective intraarterial infusion [32] . Injuries to these collateral pathways, participating in the blood supply of the hilar bile ducts, may induce ischemia of the biliary tract after liver resections and biliary surgery [28,29] .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Angiography demonstrated the interlobar branch-relayed collateral blood flow between the hepatic arteries [31][32][33][34][35][36][37] to be readily noted at the occlusion of either of the hepatic arteries [32,33,37] , which was demonstrated by computerized tomographic angiography in our Case 2 ( Figure 11). The interlobar arterial collaterals may be responsible for the poor distribution of a chemotherapeutic agent at its selective intraarterial infusion [32] . Injuries to these collateral pathways, participating in the blood supply of the hilar bile ducts, may induce ischemia of the biliary tract after liver resections and biliary surgery [28,29] .…”
Section: Discussionmentioning
confidence: 81%
“…Injuries to these collateral pathways, participating in the blood supply of the hilar bile ducts, may induce ischemia of the biliary tract after liver resections and biliary surgery [28,29] . The majority of investigators are in agreement that the interlobar collateral is extraparenchymal, passes cranial to the bifurcation of the PVs in the hepatic hilum in close proximity to the bile ducts [32,33,[37][38][39][40] and makes the crucial contribution of the blood supply to the biliary tract, as well as one of the hepatic lobes in the event of liver major route interruption [29,36,37,41] . So far it has not been clear whether there are transparenchymal branches to connect the hepatic lobes [31,33,36,42] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The interlobar arterial collateral of the liver has been thoroughly analyzed using both anatomical [12, 13] and radiological studies [14,15,16]. Our previous study showed that the communicating arcade between the right and left hepatic arteries was consistently present in the hilar plate and played an important role not only in the interlobar arterial collateral system of the liver but also in the blood supply to the hilar bile ducts [17].…”
Section: Discussionmentioning
confidence: 99%
“…sinistra als relativ risikoarme Therapie sonst unkontrollierbarer Blutungen nach Leberverletzungen. Anastomosen am Leberhilus k6nnen dann eine ausreichende Blutversorgung des betroffenen Leberlappens von der Gegenseite her gewfihrleisten [17].…”
Section: Introductionunclassified